2013
DOI: 10.1038/aps.2013.41
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide stimulates BMP-2 expression and the differentiation of human osteoblast-like cells in vitro

Abstract: Aim: To investigate whether bone morphogenic protein-2 (BMP-2) expression was involved in calcitonin gene-related peptide (CGRP)-induced osteogenesis in human osteoblast-like cells in vitro. Methods: MG-63 osteogenic human osteosarcoma cells were treated with CGRP (10 -8 mol/L) for 48 h. Cell cycle phases were determined using flow cytometry assay. The protein levels of BMP-2, ALP, Osteocalcin, ColIa1, CREB, and pCREB were measured with Western blotting, while the mRNA level of BMP-2 was measured with qR-T PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…BMP antagonist diminished the gene expression of the markers namely ALP, Collagen OPN, and total and phosphorylated Smad‐1/5/8 levels. The findings of our study with CP and VD were coherent with earlier reports where noggin influenced the expression levels of the genes ALP, Collagen, OPN and t‐Smad‐1/5/8 and p‐Smad‐1/5/8 . However, the expression levels of the OSX transcription factor were quite unpredicted after noggin treatment because the expression was completely abolished in all combination and individual groups of Dz and VD and combination groups of CP and Ge alone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…BMP antagonist diminished the gene expression of the markers namely ALP, Collagen OPN, and total and phosphorylated Smad‐1/5/8 levels. The findings of our study with CP and VD were coherent with earlier reports where noggin influenced the expression levels of the genes ALP, Collagen, OPN and t‐Smad‐1/5/8 and p‐Smad‐1/5/8 . However, the expression levels of the OSX transcription factor were quite unpredicted after noggin treatment because the expression was completely abolished in all combination and individual groups of Dz and VD and combination groups of CP and Ge alone.…”
Section: Discussionsupporting
confidence: 91%
“…Serine/threonine kinases receptors and other intracellular signaling proteins like Smads play a major role in triggering the effects at cellular level by BMP's . Amid the different BMP's, BMP‐2 both by in vivo and in vitro studies have paraded to be a crucial regulator during the bone formation and also stimulation of the differentiation of osteoblasts in an osteogenic way …”
Section: Introductionmentioning
confidence: 99%
“…6d). Further study is required to understand why RUNX2 is not responsive to magnesium or CGRP and whether other reported CREB1-regulated pathways (for example, BMP2, Wnt/β-catenin) are involved 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al claimed that CGRP participated in bone metabolism and promoted swifter fracture healing [14]. Moreover, in a recent study, Tian et al confirmed that CGRP promoted osteogenic differentiation as well as proliferation [15]. Despite various proposed mechanisms, it is certain that CGRP is a pro-osteogenic neurotransmitter.…”
Section: Introductionmentioning
confidence: 99%